Challenges of e-learning adoption in South African public schools: Learners’ perspectives - Chomunorwa, Silence; Mugobo, Virimai Victor (Journal of Education and e-Learning Research, 2023)
Educational technology (EdTech) plays a vital role in teaching and learning with e-learning ensuring equal access to education and continuity even when contact classes are impossible. The South African departments of education are making efforts to realize the use of technology in schools. The COVID-19 pandemic has an adverse impact on the education sector and accelerated the adoption of technology by many institutions with some shifting to distant learning to ensure academic continuity. There are various educational technologies. The aim of the study is to explore public high school learners’ perspectives on e-learning and the challenges in its adoption. Secondary data is used to draw conclusion. An interpretivism paradigm with an exploratory sequential mixed-method approach is used. The findings show that e-learning implementation needs careful consideration and planning. The results of this study indicate that lack of access to devices, the high cost of internet access, a perceived lack of interest among teachers and perceived ineffectiveness are the key challenges to e-learning adoption in South African public schools within poor communities. Addressing key challenges will ensure a successful implementation of e-learning.